Sense of coherence in a general adult population in Northern Norway and its associations with oral health - Kine Margrethe Mathisen; Gro Eirin Holde; Steffen Torp; Birgitta Jönsson (BMC Oral Health, 2023)
Abstract Background Sense of coherence (SOC) is a global orientation to life that may affect a person’s way of acting and living within his or her life context, which can have an impact on general and oral health. The aims of this study were (i) to describe the distribution of SOC in a general adult population; (ii) to explore whether sociodemographic characteristics, oral health-related behaviours, self-reported oral health, and clinical oral status were associated with SOC; and (iii) to explore whether SOC was associated with self-reported oral health, controlling for sociodemographic characteristics, oral health-related behaviours, and oral clinical status. Methods This study was based on data from the cross-sectional population-based study Oral Health in Northern Norway (N = 1819 individuals, 923 women, mean age 47.1 ± 15.2 years). Data were collected between October 2013 and November 2014 in Troms County. Participants answered a questionnaire that included items on SOC, sociodemographic characteristics, oral health-related behaviours, and self-reported oral health. Clinical oral status (number of teeth, dental caries, and periodontal status) was determined through oral and radiographic examination. Linear regression analysis was used to examine factors associated with SOC. Logistic regression analysis was used to examine SOC and its association with self-reported oral health adjusted for sociodemographic characteristics, behaviours, and clinical oral status. Results The mean SOC score was 68.5 (standard deviation 10.5). The younger age groups (20–29 and 30–39 years) had mean SOC scores of 64.0 (95% CI: 62.7,65.3) and 67.2 (95% CI: 66.0,68.5), respectively, and the older age groups (40–79 years) had mean SOC scores between 69.8 and 70.1 (95% CI: 68.2,71.3). A higher mean SOC score was associated with older age, higher education level, higher income (all p < 0.001), being married/cohabiting (p = 0.005), and toothbrushing ≥ 2 times/day (p = 0.008). Approximately 49% of participants reported good oral health. SOC was positively associated with self-reported good oral health in the adjusted model (odds ratio:1.03 [95% CI: 1.02,1.05] p < 0.001). Conclusions SOC was associated with sociodemographic characteristics and toothbrushing habits. There was no significant association between SOC and clinical oral status; however, SOC was positively associated with self-reported good oral health. This indicates that a person’s SOC might have an impact on how an individual perceives their oral health, independent of sociodemographic characteristics and the presence of oral diseases.